Interferência de patógenos nos resultados dos testes de vigor em sementes de feijoeiro - Frigeri, Thaís [UNESP] (2007)
The aim of this research was to verify the influence of Macrophomina phaseolina, Colletotrichum dematium f. truncata and Colletotrichum lindemuthianum in the physiological quality of bean seeds, special in the results of electrical conductivity test. There were used seeds from Carioca and FT Nobre cultivars. The seeds were artificially inoculated with fungi M. phaseolina, C. dematium f. truncata and C. lindemuthianum in BDA medium culture with and without hydric restriction (it was added -1,0 MPa manitol). In the control treatment there was used the same medium culture without the presence of the fungi. For each treatment the seeds were placed on the medium culture for 16 hours for M. phaseolina and 48 hours for C. dematium f. truncata and C. lindemuthianum. After a nature dry, seeds were evaluated, by the blotter test, sand germination and vigor tests: speed of emergence index, seedlings dry weigh, cold, accelerated aging and electrical conductivity tests. Analyses from the imbibition water of the seeds in the electrical conductivity test, were also done a measuring of concentrations of potassium, calcium and magnesium, as well as in the medium culture used with and without the seeds, to verify the hypothesis of seeds nutrients consumption by the fungi...(Complete abstract, click electronic address below)